Cantik dengan Dermal Filler dalam Sudut Pandang Kesehatan dan Maqashid Al-Shari’ah - Najie, Ilyu Ainun; Iskandar, Dede; Rahmat, Kristiawan Basuki; Husna, Sabrina Yusrin Al (Journal of Telenursing (JOTING), 2025)
This study attempts to analyze the benefits and side effects of this therapy on health, as well as its legal standing and position within Islamic law, from the perspective of maqasid al-Shari'ah (Islamic principles of Islamic law). The research employed qualitative phenomenological methods, including interviews and observations at four beauty clinics, and problem analysis using triangulation. The results demonstrate the benefits of this therapy for treating medical problems and its aesthetic benefits for skin rejuvenation. However, its potential health side effects require careful consideration of several factors, such as drug safety and the competence of the expert to avoid endangering life. The legal standing and position of both therapies, according to maqasid al-Shari'ah, are classified as tertiary needs or tahsiniyyat. In conclusion, dermal fillers are not considered an urgent need; therefore, as long as the procedure does not cause harm, their use is permissible, taking into account applicable medical aspects.   Keywords: Dermal Filler, Beauty, Maqasid al-Shari'ah, Health Promotion, Women